Die Vignette als Übung der Wahrnehmung / Nuove prospettive di professionalizzazione dell'agire pedagogico Zur Professionalisierung pädagogischen Handelns / La vignetta come esercizio di percezione - Agostini, Evi; Peterlini, Hans Karl; Donlic, Jasmin; Kumpusch, Verena; Lehner, Daniela; Sandner, Isabella (Verlag Barbara Budrich, 2023)
Pedagogical work requires the willingness to engage with new situations and with people in their diversity. This book does not offer any simple recipes, but a gentle approach to important steps towards professionalisation in the teaching profession. These lead via an open attitude of perception and the inclusion of corporeality to an insight into how learning and teaching processes can be understood in a new or different way. With vignettes and examples from different pedagogical fields, the theoretical concepts are presented and reflected on their application.